2009
DOI: 10.1128/jvi.01966-08
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory System Involvement in Natural Scrapie Disease

Abstract: The olfactory system (OS) is involved in many infectious and neurodegenerative diseases, both human and animal, and it has recently been investigated in regard to transmissible spongiform encephalopathies. Previous assessments of nasal mucosa infection by prions following intracerebral challenge suggested a potential centrifugal spread along the olfactory nerve fibers of the pathological prion protein (PrP Sc ). Whether the nasal cavity may be a route for centripetal prion infection to the brain has also been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
30
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 60 publications
2
30
1
1
Order By: Relevance
“…Whether a similar pathogenic behavior may also characterize classical and atypical scrapie under experimental or natural conditions is a matter of speculation, although the documented presence of PrP Sc and/or infectivity in the retina, tongue, and nasal mucosa during scrapie and BSE infection (15,16) would suggest that these highly innervated head districts could represent potential prion entry sites from which neuroinvasion may occur directly through the loco-regional nerve fibers, or after prion replication in the LRS. Furthermore, ruminant PTs, which are not present in rodents (17), exhibit a specialized epithelium, along with B and T lymphocytes, as well as follicular dendritic cells, which are organized into well-defined secondary follicles, thus likely creating a suitable microenvironment for the replication and the subsequent spread of prions, including the sheep scrapie agent (18).…”
mentioning
confidence: 99%
“…Whether a similar pathogenic behavior may also characterize classical and atypical scrapie under experimental or natural conditions is a matter of speculation, although the documented presence of PrP Sc and/or infectivity in the retina, tongue, and nasal mucosa during scrapie and BSE infection (15,16) would suggest that these highly innervated head districts could represent potential prion entry sites from which neuroinvasion may occur directly through the loco-regional nerve fibers, or after prion replication in the LRS. Furthermore, ruminant PTs, which are not present in rodents (17), exhibit a specialized epithelium, along with B and T lymphocytes, as well as follicular dendritic cells, which are organized into well-defined secondary follicles, thus likely creating a suitable microenvironment for the replication and the subsequent spread of prions, including the sheep scrapie agent (18).…”
mentioning
confidence: 99%
“…For this reason, major efforts have been undertaken to identify peripheral lymphoid tissues for antemortem collection and diagnosis which may exhibit sensitivities comparable to those of the brainstem/RLN, including third-eyelid, tonsil, and recto-anal mucosa-associated lymphoid tissue (RAMALT) samples (27,(32)(33)(34)(35)(36)(37). Previous studies have additionally demonstrated high levels of PrP res in olfactory epithelium and nasal secretions in several prion diseases (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48), though this prospect has not been assessed with CWD. Both RA-MALT biopsy specimens and nasal brush samples collected from the olfactory epithelium are easily and efficiently collected and processed, making these tissues promising additions in the area of antemortem detection of prion diseases and the samples of choice for our study.…”
mentioning
confidence: 99%
“…Therefore, we propose that a high concentration of prions (i.e., Ͼ10 7.5 LD 50 per ml) can be released in nasal secretions following damage to the nasal mucosa in a host with prion infection of the OSE. Additional evidence for nasal fluids as a potential source for new prion infections is based on our findings that there is a high level of prion infection in the nasal mucosa and previous studies that demonstrated PrP Sc deposition in ORNs and the olfactory nerve in natural and experimental prion diseases (10,15,17,63). In HY TME agent infection in hamsters, the amount of PrP Sc in extracts of the nasal mucosa was within 2-fold of the level in the olfactory bulb on a per protein basis in the absence of methimazole treatment, and the prion median seeding activity in these extracts was only 10-to 100-fold below the levels found in the olfactory bulb.…”
Section: Discussionmentioning
confidence: 99%
“…There are several findings to support a role for ORNs and damage to the OSE in the shedding of prions from an infected host. First, the olfactory system is a common target for prion infection in several natural and experimental prion infections, and PrP Sc has been found in the OSE, ORNs, and/or the olfactory nerve (4,10,15,17,29,30,39,63). Second, ORNs undergo continual turnover and programmed cell death, or apoptosis, throughout adult life (12,23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation